2008
DOI: 10.1371/journal.pone.0002588
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Bacteria Condition Dendritic Cells to Promote IgA Production

Abstract: Immunoglobulin (Ig) A represents the predominant antibody isotype produced at the intestinal mucosa, where it plays an important role in limiting the penetration of commensal intestinal bacteria and opportunistic pathogens. We show in mice that Peyer's Patch-derived dendritic cells (PP-DC) exhibit a specialized phenotype allowing the promotion of IgA production by B2 cells. This phenotype included increased expression of the retinaldehyde dehydrogenase 1 (RALDH1), inducible nitric oxide synthase (iNOS), B cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
96
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 56 publications
0
96
0
1
Order By: Relevance
“…The implication of our finding is that T cell-independent IgA CSR occurs in the PP at a stage before manifest GC. The fact that PP from CD40 2/2 mice hosted comparable or higher levels of gene expression for the potentially important IgA switch-factors, BAFF and APRIL (and perhaps iNOS), is important because it indicates that the PP milieu is well equipped for supporting IgA CSR, even in the absence of GC (22,26). This information coupled with the evidence of cell proliferation in the GL7 int population is the basis for proposing that the PP is the site for IgA CSR also against T cell-independent Ags.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implication of our finding is that T cell-independent IgA CSR occurs in the PP at a stage before manifest GC. The fact that PP from CD40 2/2 mice hosted comparable or higher levels of gene expression for the potentially important IgA switch-factors, BAFF and APRIL (and perhaps iNOS), is important because it indicates that the PP milieu is well equipped for supporting IgA CSR, even in the absence of GC (22,26). This information coupled with the evidence of cell proliferation in the GL7 int population is the basis for proposing that the PP is the site for IgA CSR also against T cell-independent Ags.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to CSR in peripheral lymph nodes or the spleen, the former relies on the formation of germinal centers (GCs) and is dependent on CD40 and TGFb, whereas the latter occurs in the absence of GC, is independent of CD40, and is supported by production in situ of inducible NO synthase (iNOS), B cell activating factor of the TNF (BAFF), and a proliferation inducing ligand (APRIL) by epithelial cells, dendritic cells (DCs), or stromal cells (21)(22)(23)(24)(25)(26). Whereas IgA production is near normal in the absence of CD40, it is dramatically impaired in APRIL-or BAFF-deficient mice (27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Previous studies have been made to identify the cDCs responsible for inducing IgA secretion by secreting IgA-inducing factors (BAFF, APRIL, iNOS, RALDH1, IL-6, TGF-β et al). [23][24][25] However, whether co-immunization of chitosan-pAIM2 with chitosanpVP1 could enhance pDCs recruitment and maturation as well as the expression of IgA-inducing factors in MLN is unclear. According to our results, AIM2 co-immunization also enhances CD40, CD80, and MHCII expression on DCs in MLN.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Thus, we determined the amount of DCs recruited into MLN during chitosan-pAIM2 and chitosan-pVP1 co-immunization. It was found that compared with chitosanpVP1 immunization alone, chitosan-pAIM2 co-immunization not only increased the percentage (10.80% vs 21.91%, P < 0.01) and number (3.91 × 10 4 vs 7.16 × 10 4 , P < 0.01) of CD11c + DCs in the MLN sites (Fig.…”
Section: Increased Mln Dcs Recruitment and Iga-inducing Factor Expresmentioning
confidence: 99%
“…Selective deficiency of IgA is the most common form of primary immunodeficiency in the West and can result in recurrent pulmonary and gastrointestinal infections. 4 IgA is produced in the spleen and gut-associated lymphoid tissues (including the PP) by activated B cells and plasmablasts from two sources: (i) the T cell-independent effects of dendritic cell-derived APRIL and BAFF on 'innate like' B1 cells; 5 and (ii) the influence of TGFb and cognate T cell help on (conventional) B2 cells. [6][7][8] Even in the complete absence of ab-T cells, 9 isotype switching and protective antibody production occurs, 7,8 reflecting the relative robustness of T-independent antibody production.…”
mentioning
confidence: 99%